Crossbreeding influence on age at first calving and first lactation productivity in Lithuania bred dairy cattle - Petra?kien?, Rasa; Pe?iulaitien?, Nijol?; Jukna, Vigilijus (Cuban Journal of Agricultural Science, 2011)
This paper provides records of milk production of first calving and age at first calving of 2227 pure Holstein cows, 301 Danish Red cows, 522 Red Holstein cows, 261 Swedish Red cows, 143 crosses of Holstein cows with Danish Red sires (HxDR), 363 crossbreeds of Holstein cows with Swedish Red sires (HxSR), and 135 crossbreeds of Holstein cows with Red Holstein sires (HxRH). There was higher percentage of milk proteins of 0.2 % in HxDR crossbreds and of 1.1 % in HxSR (P < 0.01) crossbreds. The other traits of higher productivity were in Holstein cows. The crossbreeding had a positive effect on age at first calving in the crossbreds, and is much lower than that in purebreds. The lowest age at first calving in days was found in the HxDR crossbreds. This difference was of 33.3 d or 4.2 % (P < 0.001), compared with the pure Holstein breeds. Also, the first lactation, fat and protein content and yield of recalculated milk were higher in pure red cows compared with crossbreds. However, according to these results, the HxRH crossbreds (64.4 d or 8.2 %) (P < 0.001) matured earlier than the pure Red Holstein cows. Therefore, dairy cattle crossbreeding may be used if the goals are not only for milk production but also age at first calving, fertility, welfare, and longevity improvement. Key words: heterosis effects, milk production, cattle.